The Effect of Servise Quality of Old Age Security Program on Customer Satisfaction of Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Branch Office of Makassar - Suci Lestari B; Hasnawi Haris; Aris Baharuddin; Muhammad Guntur; Jamaluddin Jamaluddin (Universitas Negeri Makassar, 2021)
Every public service must have service standards and be published as a guarantee of certainty for service recipients. That way through good service, customers will feel valued and do not feel neglected and finally customers as recipients of services offered by government-owned agencies will feel satisfied. This study aims to determine how the influence of the service quality of the old-age insurance program on the satisfaction of the participants of the Social Security Administration for Employment at the Makassar Branch Office. This study uses a quantitative approach with descriptive research type. Data collection techniques are carried out through observation and questionnaires/ questionnaires. The population in this study was 216,014 people by taking 10% of the sample as many as 100 people using the incidental sampling technique. The analytical method used is descriptive statistical analysis and inferential analysis. The results showed that the indicators used in each variable indicated that the quality of BPJS Ketenagakerjaan services at the Makassar Branch Office was in the very good. And for the satisfaction of BPJS Ketenagakerjaan participants, the Makassar branch office is in the high. Meanwhile, based on the correlation test, that there is a strong / high correlation between the two variables. Soit can be concluded that there is a significant influence between the service quality of the old age insurance program on the satisfaction of participants in Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Branch Office of Makassar.